LEGAL CULTURE AND DEMOCRATIC DEVELOPMENT: ISSUES OF DIALECTICAL DEPENDENCE - Abdurakhmanova Nadirahan Husnutdinovna (Journals Park Publishing, 2022)
This article discusses the dialectical relationship between democratic development and legal culture.
Keywords: law, legal knowledge, legal culture, legal activity